2008
DOI: 10.1089/oli.2008.0112
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Murine Neuroblastoma by Systemic Delivery of Transferrin-Shielded siRNA Polyplexes for Downregulation of Ran

Abstract: The polymer, OEI-HD, based on beta-propionamide-cross-linked oligoethylenimine and its chemical transferrin conjugate were evaluated for siRNA delivery into murine Neuro2A neuroblastoma cells in vitro and in vivo. An 80% silencing of luciferase expression in neuroblastoma cells, stably transfected with a luciferase gene, was obtained using standard OEI-HD polyplexes or transferrin-conjugated shielded OEI-HD polyplexes. The Ras-related nuclear protein Ran was selected as a therapeutically relevant target protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…Gene Silencing Effect of MENDs To examine the silencing effect of the MEND, 4ϫ10 4 HeLa-luc cells were seeded in a 24-well dish 1 d prior to transfection. The MEND, containing the indicated dose of siRNA, was added to 0.25 ml of DMEM containing 10% FBS, followed by incubation at 37°C for 3 h. Then, 0.75 ml of DMEM containing 10% FBS was added to the cells, followed by incubation for an additional 21 h. The cells were then washed with 0.5 ml of PBS and lysed with reporter lysis buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene Silencing Effect of MENDs To examine the silencing effect of the MEND, 4ϫ10 4 HeLa-luc cells were seeded in a 24-well dish 1 d prior to transfection. The MEND, containing the indicated dose of siRNA, was added to 0.25 ml of DMEM containing 10% FBS, followed by incubation at 37°C for 3 h. Then, 0.75 ml of DMEM containing 10% FBS was added to the cells, followed by incubation for an additional 21 h. The cells were then washed with 0.5 ml of PBS and lysed with reporter lysis buffer.…”
Section: Methodsmentioning
confidence: 99%
“…To address these issues, many groups have developed various types of carrier systems for siRNA delivery, such as lipoplexes and polyplexes. [3][4][5] We recently proposed a novel packaging approach for the assembly of multiple devices in a single delivery system, a multifunctional envelope-type nano device (MEND), in which nucleic acid is condensed using a polycation to form a core particle, followed by encapsulation in a lipid envelope. 6,7) When the MEND was modified with stearylated octaarginine (STR-R8) on the lipid envelope (R8-MEND), it was efficiently taken up by cells via a unique pathway called macropinocytosis, which allowed escape from lysosomal degradation and led to transfection activity as high as that of adenovirus.…”
mentioning
confidence: 99%
“…The advantage of using PEI compared to PLL is the high transfection efficiency due to the buffering capability at the low pH of the lysosome inducing the 'proton sponge effect' (Mintzer and Simanek, 2009). However, it has been reported that PEI which escapes the endosome/lysosome can enter the nucleus where it may potentially disrupt endogenous gene expression (Godbey et al, 1999 PEI derivatives for siRNA delivery have been designed to increase hydrophility, reduce cytotoxity, and enhance transfection efficacy using substitution of degradable moieties and copolymers ( [Meyer et al, 2008], [Zintchenko, et al, 2008], [Tietze et al, 2008], and ). For instance, beta-propionamide-cross-linked oligoethyleneimine with a transferrin targeting ligand has been shown to successfully deliver siRNA by intravenous administration, and three treatments of the polymer/siRNA complex resulted in more than 80% reduction in target protein expression levels (Tietze et al, 2008).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…However, it has been reported that PEI which escapes the endosome/lysosome can enter the nucleus where it may potentially disrupt endogenous gene expression (Godbey et al, 1999 PEI derivatives for siRNA delivery have been designed to increase hydrophility, reduce cytotoxity, and enhance transfection efficacy using substitution of degradable moieties and copolymers ( [Meyer et al, 2008], [Zintchenko, et al, 2008], [Tietze et al, 2008], and ). For instance, beta-propionamide-cross-linked oligoethyleneimine with a transferrin targeting ligand has been shown to successfully deliver siRNA by intravenous administration, and three treatments of the polymer/siRNA complex resulted in more than 80% reduction in target protein expression levels (Tietze et al, 2008). In addition, a newly developed siRNA vector comprising PEI grafted to hyaluronic acid (HA) via a disulfide linkage (PEI-SS-HA) was described and this non-toxic vector enhanced the serum stability of siRNA, facilitated specific cellular uptake by the HA receptor through endocytosis, and more importantly intratumoural injection of this complex significantly suppressed tumour development with decreased VEGF mRNA and protein expressions .…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…[219] In addition to nontargeting vector/DNA polyplexes, different vector systems were developed to promote delivery into specific cell populations by incorporation of cell targeting moieties into the vector system. [168,[228][229][230][231] These moieties/ligands (e.g., transferrin, [168,[232][233][234][235][236][237][238][239] epidermal growth factor (EGF), [236,240] arginine-glycine-asparagine (RGD), [241][242][243][244][245] and folate), [242,[246][247][248][249][250] recognize cell type specific receptors in order to direct cellular uptake via receptor-mediated endocytosis, as illustrated in Figure 18. Once bound to the receptors on the cell surface, the vector/DNA polyplexes are internalized by clathrin-dependent endocytosis.…”
Section: Clathrin-mediated Endocytosis (Cme) Is Crucial For Intercellmentioning
confidence: 99%